Integration of Sharia Insurance and Islamic Banking to Achieve a Sustainable Economy - Hayfa Azwa Fadhila; Kusmilawaty Kusmilawaty; Nuri Aslami (SAINTIS Publishing, 2025)
This study aims to analyze the integration between Islamic insurance and Islamic banking in supporting a sustainable economy. The research method used is a qualitative approach with a literature review technique, utilizing secondary data sources from scientific journals, official reports, and relevant laws and regulations. The results show that the integration between Islamic insurance and Islamic banking can be seen in strategic collaboration in product marketing (bancatakaful), as well as their role in sustainable financing through Islamic investment instruments such as green sukuk. This integration encourages the creation of risk protection for customers, strengthens green financing portfolios, and increases Islamic financial inclusion. However, challenges remain, such as low public financial literacy, regulatory disharmony between institutions, and limitations in information technology. Therefore, collaborative efforts are needed between the government, industry players, and the community to realize an inclusive and sustainable Islamic financial system in Indonesia.